PP.39.02: DISTRIBUTION OF ETIOLOGIES OF RENAL ARTERY STENOSIS IN 2047 CHINESE INPATIENTS. A SINGLE-CENTER RETROSPECTIVE ANALYSIS DURING A 15-YEAR PERIOD. (June 2015) - Jiang, X.; Peng, M.; Dong, H.; Zou, Y.; Song, L.; Zhang, H.; Wu, H.; Liu, L.
Abstract : Objective: To investigate the distribution of etiologies of renal artery stenosis in Chinese inpatients diagnosed with renal artery stenosis. Design and method: We retrospectively analyzed the etiology of RAS in 2047 consecutive inpatients diagnosed with RAS. Patients presented for hypertension work-up at Fuwai hospital between March, 1999 and June, 2014. Results: Atherosclerosis was the cause of RAS in 1668 (81.5%) patients, Takayasu's arteritis (TA) in 259 (12.7%) patients, FMD in 86 (4.2%) patients, other causes were present in 34 (1.6%) patients. There was an obvious increase with age in the proportion of atherosclerotic RAS (P < 0.01). In patients aged less than 40 years (n = 319) the predominant etiology of RAS was TA (60.5%), followed by FMD (24.8%). In patients aged over 40 years (n = 1728) the major cause of RAS was atherosclerosis(94.7%), followed by TA(3.8%). The proportion of TA and FMD in female patients was significantly higher than that in male patients (P < 0.01). In female patients aged less than 40 years (n = 215), the top three etiologies of RAS were TA (68.4%), FMD (27.9%) and atherosclerosis (1.4%). In male patients aged less than 40 years (n = 104), the order of the etiology of RAS was TA (44.2%), atherosclerosis (26.9%) and FMD (18.3%). Conclusions: This patient analysis showed atherosclerosis, TA and FMD were successively the top three causes of RAS in a Chinese population. Age and gender had a significant effect on the distribution of etiologies of RAS.